PENGARUH TINGKAT KETERGANTUNGAN PENGELUARAN PEMERINTAH DIBIDANG PENDIDIKAN DAN BIDANG KESEHATAN TERHADAP KEMISKINAN KOTA PAREPARE - T, Ruslang; Alwi, Muh.; Jurhana, Jurhana (Cateris Paribus Journal, 2022)
Poverty in developing countries is a fairly complicated problem even though several developing countries have succeeded in carrying out development in terms of production and national income. This study aims to determine the effect of the dependency ratio, the effect of government spending on education and health on poverty in the Parepare City. This research method is a quantitative descriptive study that uses secondary data in the form of a time series from the poverty data of the Parepare City for 2014-2019 period as well as government spending in the education and health sectors of the Parepare City for 2014-2019 period. The analytical technique used in this study is multiple linear regression analysis using the SPSS 16 application.